THE INFLUENCE OF CREATIVITY, TECHNOLOGY INTEGRATION SELF-EFFICACY, AND ADVERSITY QUOTIENT ON INTENTION TO BE A TEACHERPRENEUR WITH INTERPERSONAL COMMUNICATION AS A MODERATING - Siswi Putri Sulawartisari; Kardiyem Kardiyem (Jurnal Pendidikan Akuntansi Indonesia, 2023)
The purpose of this study is to determine and analyze the effect of creativity, technology integration self-efficacy (TISE), and adversity quotient on the intention to become a teacherpreneur in Accounting Vocational School teachers in Pemalang Regency. This variable is moderated by interpersonal communication as a moderating variable. The population of this study are all teachers of Accounting Vocational Schools in Pemalang Regency, which amounted to 93 teachers. The sampling technique uses a saturated sample technique. The number of research samples are 85 respondents. The data were analyzed using descriptive statistical analysis and Moderate Regression Analysis (MRA), using IBM SPSS Statistics 25 for windows software. The results of the analysis obtained in this study indicate that the intention to become a teacherpreneur is influenced by creativity, TISE, and adversity intelligence. Furthermore, interpersonal communication is only able to strengthen the relation between the influence of creativity on the intention to become a teacherpreneur.  Keywords: Adversity Quotient, Creativity Intention Teacherpreneur, Interpersonal Communication, Technology Integration Self-Efficacy (TISE).